1997
DOI: 10.1021/ja9715096
|View full text |Cite
|
Sign up to set email alerts
|

CO Binding to the FeMo Cofactor of CO-Inhibited Nitrogenase:  13CO and 1H Q-Band ENDOR Investigation

Abstract: The resting state of nitrogenase shows an S = 3/2 electron paramagnetic resonance (EPR) signal resulting from the FeMo-cofactor (MoFe7S9:homocitrate) of the MoFe protein. When the enzyme undergoes turnover under a CO atmosphere, this signal disappears and two new ones appear:  one under low pressure of CO (denoted lo-CO; 0.08 atm) and the other under high pressure of CO (denoted hi-CO; 0.5 atm). Our recent Q-band (35 GHz) 13C and 57Fe electron nuclear double resonance (ENDOR) studies demonstrated that one CO i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
195
2
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(216 citation statements)
references
References 44 publications
17
195
2
2
Order By: Relevance
“…Several earlier studies have suggested two binding sites on FeMo cofactor. For example, it has been proposed that two CO molecules bind to FeMo cofactor in the high CO concentration inhibited state (29)(30)(31)(32)(33). Likewise, two acetylene binding sites have been implicated from studies combining kinetics and amino acid substitutions (31,34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several earlier studies have suggested two binding sites on FeMo cofactor. For example, it has been proposed that two CO molecules bind to FeMo cofactor in the high CO concentration inhibited state (29)(30)(31)(32)(33). Likewise, two acetylene binding sites have been implicated from studies combining kinetics and amino acid substitutions (31,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies revealed multiple inhibitor and substrate binding sites on FeMo-cofactor, including at least two binding sites for CO (29)(30)(31)(32)(33) and acetylene (31,34,35). Two adjacent binding sites can explain the earlier reports that two or three CO molecules can be reduced and coupled to form C2 and C3 hydrocarbon products (24,26).…”
Section: Co 2 Reduction To Chmentioning
confidence: 95%
“…As a result, some 2,000 non-fire-related CO-poisoning deaths occur annually in the United States (92). Human toxicity is attributed to the high affinity of CO for iron such that the oxygen capacity of hemoglobin is reduced, and the gas is broadly inhibitory for heme proteins and nonheme iron enzymes including hydrogenase (2,45,106) and nitrogenase (20,83,106). In light of its heme affinity, it is a biological irony that the primary endogenous source of CO in mammals is heme degradation catalyzed by multiple heme oxygenase activities in the cell.…”
Section: Sources and Biological Impacts Of Comentioning
confidence: 99%
“…First, as detailed below, the purified protein shows a significant response to CO. Second, the response of FixL to a variety of small-molecule ligands serves as a useful counterpoint to the extreme ligand specificity of CooA. Finally, because CO is a potent inhibitor of nitrogenase (20,83), the notion of a physiologically significant response by FixL to CO is not preposterous.…”
Section: Fixlmentioning
confidence: 99%
“…Hoffman and coworkers have been able to demonstrate that CO can bind to iron sites on the FeMo-cofactor under turnover conditions through ingenious spectroscopic experiments utilizing isotopically substituted CO and cofactor (64). These studies have been interpreted in terms of multiple binding modes of the CO to the cofactor that vary in affinity and bonding interactions (65). CO binding to the MoFe-protein has also been monitored by stopped-flow infrared spectroscopy, which again indicates the binding of multiple COs to a metallocluster (66).…”
mentioning
confidence: 99%